Does environment and health awareness matter for household fuel choice? Empirical evidence from Central Asia - Dina Azhgaliyeva; Wataru Kodama; Hans Holzhacker (Asian Development Bank Institute (ADBI), 2023)
Household consumption of coal and other dirty fuels for heating and cooking greatly contributes to air pollution both outdoors and indoors. This paper contributes to the literature on the determinants of household heating choice (dirty versus modern energy source). Energy transition in countries where a large proportion of the population is energy-poor could be challenging. To investigate the energy choice of the energy-poor population we conducted a survey with 1,522 households from three countries in Central Asia: eastern Uzbekistan, the southern Kyrgyz Republic, and northern Tajikistan (also called Fergana Valley). Half of the households (50%) use coal for heating. We find that the energy-poor (who comprise 66% of the population) are more likely to use dirty fuel for heating. The determinants of heating choice (dirty fuel versus modern energy) vary for the energy-poor and energy-non-poor. For example, households that care about environmental harm are less likely to choose dirty fuel for heating, but only among those who are energy nonpoor. Awareness of health impacts has a significant effect on the heating fuel choice across all groups (energy-poor and -nonpoor). Based on the above findings, policy recommendations for promoting the transition from dirty to modern heating are provided.
Keywords: G50; G51; G53; 330; fossil fuel; heating; energy-poor; Central Asia; household energy consumption; energy transition